JUS MENTIMUN: ALTERNATIF PANGAN LOKAL UNTUK PENGENDALIAN HIPERTENSI PADA KEHAMILAN - Evy Kasanova; Lidia Widia; Riski Muji Lestari; Wardah Wardah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Introduction: Hypertension is a chronic health problem of major concern due to its increasing prevalence and impact on morbidity and mortality. Cucumber, also known as Cucumis sativus, is a local food ingredient readily available. Methods: This study involved providing health education to patients and their families and administering cucumber juice for 7 days. Evaluation was based on blood pressure measurements. Results: Blood pressure decreased following health education and cucumber juice consumption, and mothers and families improved their understanding of hypertension, its risk factors, and complications. They also gained a better understanding of the importance of self-administering non-pharmacological hypertension treatment at home. Conclusion: Mothers demonstrated a decrease in blood pressure after administering 200 ml of cucumber juice daily for seven consecutive days.